2008
DOI: 10.1097/gme.0b013e3180dca175
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin for the treatment of menopausal hot flashes

Abstract: Gabapentin at 900 mg/day is an effective and well-tolerated treatment for hot flashes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 32 publications
1
68
0
3
Order By: Relevance
“…In a clinical experiment, Butt et al [11] showed that 300 mg gabapentin three times per day (i.e. 900 mg/day) for 4 weeks significantly reduced the frequency of hot flashes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a clinical experiment, Butt et al [11] showed that 300 mg gabapentin three times per day (i.e. 900 mg/day) for 4 weeks significantly reduced the frequency of hot flashes.…”
Section: Discussionmentioning
confidence: 98%
“…Gabapentin is an antiseizure medication that reduces VMS [10,11]. Fluoxetine has also been reported to reduce the symptoms of hot flashes when used for treatment of depression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Advantages include no significant drug interactions, associated sexual dysfunction, or withdrawal symptoms. Disadvantages include dizziness, unsteadiness, and drowsiness in up to 20% of patients 46 . Clonidine can be helpful in patients with mildmoderate hot flushes.…”
Section: Treatment Updates: Care Of the Breast Cancer Survivormentioning
confidence: 99%
“…La dosis recomendada para el tratamiento de los sofocos es de 900 mg/día (54) . Dentro de los efectos adversos, aproximadamente al 20% de las pacientes refieren somnolencia, mareos y cierta anhedonia; aparecen luego de la primera semana de tratamiento y se resuelven espontáneamente luego de la cuarta semana de uso (55) .…”
Section: La Sociedad Internacional De Menopausia (Ims)unclassified